Study of the Cost of Economic and Human Labor Losses in a Plastics Manufacturing Company - Vélez-Barzallo, Julio César (2015)
The present research work was carried out with the aim of determining the economic cost of work-related accidents occurred but reported to the insurance General risks of labour (SGRT) from 2012 in the company Rhenania S. A., which was established to conduct the study by applying research methods that are appropriate for this purpose. The survey was carried out to 100% of the working population and found that 49 labour incidents and 21 work-related accidents over the past years have occurred, but the cases reported to the SGRT from the year 2012 have been 3 labour incidents and accidents 8. A calculation methodology was designed to value in economic terms the incidents and accidents, resulting in a cost of 33.257,37 dollars, of which 689, 58 dollars corresponded to labour incidents and 32.567,79 dollars corresponded to accidents. These values to percent was 9.9178 corresponds to the pay part, 2.62956 a part of health and 87.47% a part of productivity. On the basis of information obtained from research, the company should take measures on maintenance of machinery and necessary in terms of occupational health and safety prevention to prevent incidents and accidents.